Selected Papers from the 3rd International Symposium on Life Science - Stonik, Valentin A. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book contains information for specialists in various fields of science. From the point of view of pharmacology, data are reported regarding the effect of echinochrome A and related metabolites from sea urchins on the survival and functional properties of stem cells, which can facilitate ex vivo application of this compound in medicine. For scientists who isolate and establish structures of marine natural compounds, an article devoted to the proof of the microbial origin of a typical metabolite earlier found exclusively from marine invertebrates, 6-epi-monanchorin, may also be of interest. A range of new marine metabolites was discovered from the both marine invertebrates and marine microorganisms, particularly in marine isolates of fungi. Some marine natural products could be applied to treat such diseases as Parkinson's disease, ischemic stroke, viral infections, and so on. Magnificamide, a new peptide from sea anemones, inhibits porcine and human saliva amylases, showing its probable antidiabetic properties. Application of the genomic approach was discussed in studies on various marine bacteria, producing marine enzymes with unusual specificity. The lectins capable of recognizing glycoforms of different substrates demonstrate the possibility to be used to elaborate new medical diagnostics.